Strategi Perintah Daerah Kabuoaten Sintang dalam Mewujudkan Visi Pemerintahan dan Good Governance - Mardawani, Mardawani; Relita, Dessy Triana (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This paper aims to discuss the programs carried out in realizing the vision of the Sintang District Government and the strategy to achieve good governance by the Sintang District Government. The study uses qualitative descriptive with case studies. Sintang District Government achieved the vision through programs that focus on the realization of smart, healthy, advanced, religious, and prosperous community and implements good and clean governance. The strategy undertaken by the Local Government of Sintang District to achieve good and clean governance is carried out in five stages, namely consolidation, strengthening, acceleration, development, and consolidation carried out consecutively from 2017 to 2021.